Penilaian Kondisi Bangunan pada Salah Satu Gedung Perkantoran Jakarta dalam Pengambilan Keputusan dan Pengaruh Keselamatan Para Pekerja - Pandu Wicaksono; Rizka Novembrianto (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Assessment of building conditions is a method of evaluating a building objectively in the form of a scale of 1-100 based on the performance of the building system that composes it. The purposes of this assessment are (1) Knowing the condition of the building; (2) Reconstructing the maintenance planning strategy to reduce the amount of damage in the following evaluation period (3) Re-assessing the impact of operational damage on the work environment. The research phase begins with (1) grouping buildings that have the same function; (2) Determining the range of data and categorization; (3) Conducting inspections and data collection; and (4) Data analysis. Before an appraisal of a building, the appraiser needs the initial cost of the building during the construction process. If the initial cost of the building is not well documented, the cost of building construction is obtained by calculating estimates. Through estimation calculations, appraisers can determine the factors that can affect the evaluation process of a building. Determination of the initial cost is calculated based on a sample that has been grouped by function and purpose. The results obtained will be able to assist in making decisions for scheduling maintenance and inspections, functional and re-design of buildings, or OHS (Ocupational Health and Safety) evaluation reviews.